Metal Chaperones: A Holistic Approach to the Treatment of Alzheimer’s Disease - Adlard, Paul A.; Bush, Ashley I. (Frontiers in Psychiatry, 2012)
As the burden of proof for the role of metal ion dysregulation in the pathogenesis of multiple CNS disorders grows, it has become important to more precisely identify and differentiate the biological effects of various pharmacological modulators of metal ion homeostasis. This is particularly evident in disorders such as Alzheimer’s disease, where the use of metal chaperones (that transport metals), as opposed to chelators (which exclude metals from biological interactions), may prove to be the first truly disease modifying approach for this condition. The purpose of this mini-review is to highlight the emerging notion that metal chaperones, such as PBT2 (Prana Biotechnology), modulate a variety of critical pathways affecting key aspects of the AD cascade to provide a more “holistic” approach to the treatment of this disease.